FEATURES OF THE DEVELOPMENT OF THE REFLEXIVE POSITION OF STUDENTS IN THE CONDITIONS OF DISTANCE EDUCATION - Nuraly, A.Zh. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
The article describes the current trend in the development of the reflexive position of students in the context of distance education. The article describes the significant role of feedback in the context of a pandemic. Purpose: to study the reflexive position of students in the context of distance education
Keywords: distance learning; reflexive attitude; feedback; motivation; emotional state